Discourse-level structuring of information in narrative:Signalling structural, interactional and cognitive shifts - Tuija Virtanen (Discours)
Discourse-level structuring of information is explored in narrative in the light of three parameters subsumed under this umbrella notion: (i) the structural concepts of “theme-rheme”, connected to “position”; (ii) the interaction-oriented pair of concepts “topic-comment”, grounded in the notion of “aboutness”; and (iii) the cognitively motivated gradient from “given” to “new” information, related to interlocutors’ assumptions of their memory constraints as well as those of others. In each pair/gradient of concepts one member/pole – “theme”, “comment”, and “new” – is argued to constitute the Figure, against the (necessary) Ground of the other. The linguistic signalling of the structural, interactional and cognitive shifts in information structuring is examined in two different kinds of narratives in written French. The analysis of a short legend, in its entirety, and a narrative paragraph from a news story both point to high context-sensitivity in the signalling of the three parameters of discourse-level structuring of information, with that of the discourse level “newness” differing most markedly from the others.